Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada - Robinson, Ian (Relations industrielles / Industrial Relations, 2013)
Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada, edited by John Peters, is reviewed.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Changes; Corporate culture; LABOR market; Labor Unions; Neoliberalism; Political economy; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z